Analisis Struktur Modal Pada PT.Bank Sulut Manado - umboh, angela mailoa (ACTA DIURNA KOMUNIKASI, 2012)
Abstract : Optimal capital structure is a balance between the use of their own capital with long-term loans; intention is how much of their own with the use of long-term loan that will be used so that it can optimal.Struktur capital or funding decisions will greatly affect the performance of the company. The purpose of this study is as follows: "To determine the capital structure made in PT. Bank of North Sulawesi, Manado. "Capital is a power in the form of money or capital goods that have not been used, which are recorded in the balance sheet and to the next debit is kredit.Struktur capital financing to strengthen the capital structure of the company do with its own capital and sourced of long-term debt. In this research method digunakanadalah descriptive method of using the table, the financial statements are based on financial ratios Perusahaan.Yang approach the target of the object of this study is to analyze Manado.Dalam PT Bank Sulawesi in PT Bank Sulawesi capital structure ratio, the formula ratio used is Leverage ratio. This ratio indicates how far a company luar.Pada difinansier by the total liabilities (total liability) encountered kenaikkan.Pada the capital (equity) in 2011, the total capital of the company PT. Bank of North Sulawesi had kenaikan.Pada the profit and loss statement in 2011. Decline in strengthening the capital structure of the PT. Bank of North Sulawesi, efforts should be made for additional capital through the sale of shares as an increase in income from operation sand other businesses. Keywords: capital structure.